Dampak Fitur Augmented Reality Tirtir Terhadap Brand Engagement dan Usage Intention: Melalui Lensa Technology Acceptance Model Dalam Pemasaran Produk Kecantikan - Dreena Alvina Roselynd; Ahmad Hamdani; Jerry S. Justianto (LPPM Institut Pendidikan Nusantara Global, 2025)
This study analyzes the impact of Augmented Reality (AR) features of the Tirtir brand on Brand Engagement and Usage Intention through the Technology Acceptance Model (TAM). A survey was conducted with 377 female TikTok users in the Greater Jakarta area (Jabodetabek), and the data were analyzed using SEM-PLS. The results show that AR characteristics (Vividness, Interactivity, Novelty) have a significant positive effect on Perceived Ease of Use, Perceived Usefulness, and Enjoyment. These three variables positively influence Brand Engagement, which in turn affects Brand Usage Intention. The study confirms the mediating role of TAM variables in the relationship between AR characteristics and Brand Engagement, as well as the mediating role of Brand Engagement in the relationship between TAM variables and Brand Usage Intention. The findings provide strategic implications for digital marketing in the beauty industry through interactive virtual shopping experiences.